TGF-β neutralization abrogates the inhibited DHEA production mediated by factors released from M. tuberculosis-stimulated PBMC - D'attilio, Luciano David (2012)
Supernatants (SN) from cultures of peripheral blood mononuclear cells (PBMC) of tuberculosis (TB) patients inhibit dehydroepiandrosterone (DHEA) secretion by the adrenal cell line NCI-H295R. To analyze whether TGF-β is involved in this effect, SN of PBMC from healthy controls or patients with severe TB infections, stimulated or not with Mycobacterium tuberculosis (Mtb SN), were added to adrenal cells under basal conditions or following stimulation with forskolin. Cortisol and DHEA concentrations were evaluated in supernatants of the adrenal cells cultured with or without the addition of anti-TGF-β. Treatment with Mtb SN from TB inhibited DHEA production, and this effect was reversed when SN were treated with anti-TGF-β. The increase in cortisol production induced by SN from TB patients was not affected by TGF-β neutralization. Mediators released during the anti-TB immune response differentially modulate steroid production by adrenal cells, and TGF-β is a cytokine implicated in the inhibition of DHEA production observed in TB.